Technological Innovation in Influence the Financial Performance of Sharia Banking In Indonesia - Razali Ade Syahputra Hasibuan; Ulfi Kartika Oktaviana (ITB AAS INDONESIA Surakarta, 2023)
This study measures how the role of innovation in technology in moderating efficiency and competition affects financial performance. This study uses secondary data which was conducted at 14 Islamic Commercial Banks in Indonesia which were taken using the non-probability sampling method in the form of purposive sampling from 2013-2020. The data analysis technique used is panel data regression analysis. The results obtained are that efficiency has a significant negative effect on financial performance, competition has a significant negative effect on financial performance, technological innovation can moderate efficiency and competition on the financial performance of Islamic banking in Indonesia.